2009
DOI: 10.1016/j.yebeh.2009.02.036
|View full text |Cite
|
Sign up to set email alerts
|

Curing epilepsy: Progress and future directions

Abstract: During the past decade, substantial progress has been made in delineating clinical features of the epilepsies and the basic mechanisms responsible for these disorders. Eleven human epilepsy genes have been identified and many more are now known from animal models. Candidate targets for cures are now based upon newly identified cellular and molecular mechanisms that underlie epileptogenesis. However, epilepsy is increasingly recognized as a group of heterogeneous syndromes characterized by other conditions that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
85
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 111 publications
(89 citation statements)
references
References 144 publications
2
85
0
Order By: Relevance
“…Because epilepsy is a complex disease, genetic influences as causal factors of the epilepsies can point the way to new treatment strategies. On the basis of these facts, an elegant study recently reviewed the progress in this area and suggested specific goals that once accomplished promise to lead to cures for epilepsy 11 . Thus, at least 11 genes have now been described for human epilepsy and over 50 more genes have been identified in animal models of epilepsy [11][12][13] .…”
Section: Resumo -Em 12 De Fevereiro De 2009 Nós Comemoramos O Aniversmentioning
confidence: 99%
See 4 more Smart Citations
“…Because epilepsy is a complex disease, genetic influences as causal factors of the epilepsies can point the way to new treatment strategies. On the basis of these facts, an elegant study recently reviewed the progress in this area and suggested specific goals that once accomplished promise to lead to cures for epilepsy 11 . Thus, at least 11 genes have now been described for human epilepsy and over 50 more genes have been identified in animal models of epilepsy [11][12][13] .…”
Section: Resumo -Em 12 De Fevereiro De 2009 Nós Comemoramos O Aniversmentioning
confidence: 99%
“…On the basis of these facts, an elegant study recently reviewed the progress in this area and suggested specific goals that once accomplished promise to lead to cures for epilepsy 11 . Thus, at least 11 genes have now been described for human epilepsy and over 50 more genes have been identified in animal models of epilepsy [11][12][13] . Alternatively, the specialists believe that the progress in understanding epilepsies of complex genetic origin will require not only identification of individual susceptibility alleles and analysis of gene to gene interactions, but also the study of gene-environment interactions 11 .…”
Section: Resumo -Em 12 De Fevereiro De 2009 Nós Comemoramos O Aniversmentioning
confidence: 99%
See 3 more Smart Citations